Green buildings in tropical countries (low-rise residential buildings) - Turiano, Timothy John Bitonio (2019)
This report explores green building design and features found in the tropical region. Energy consumption is reduced through the use of active and passive design systems in a green building. This report will analyze several green features found in buildings in the tropics as well as Singapore’s energy consumption to show the need to build energy efficient houses. The schemes introduced by government agencies, NEA and BCA will be highlighted in this report. Green mark and mandatory energy labeling schemes encourages built industry partners as well as individuals to have a role in building a sustainable Singapore. Three case studies are presented in this report to illustrate the use of green building design and features. 1. BCA-Zero Energy Building serves as a blueprint for future sustainable low-rise residential building design. 2. HAUS@Serangoon Gardens presents a modern residential green building model that uses advanced and innovative technology. 3. Traditional Malay House illustrates the use of primitive design and building methods that predominantly uses passive design systems to achieve thermal comfort. The proposed low-rise residential building is a fully detached landed property housing in Singapore. The house uses green building designs and features such as maximizing the orientation and shape, efficient ventilation, energy saving devices and the use of suitable materials for the building envelope. The proposed house aims to achieve energy efficient design by reducing the need for heating, ventilation and air-conditioning while producing electricity to offset some of its electricity consumption. Lastly, this report will evaluate the present and future application of green features in Singapore’s low-rise residential buildings by understanding the factors that influence the use of green features and how it can lead to sustainable development.